(untitled) (Development Service Industry Management, 2025)
The article highlights the essence, structure and principles of resource provision of enterprise activities, approaches to the definition of the category “resource provision”. The security aspects of resource provision of enterprises and factors influencing its security resource provision are characterized. Among the components of the security aspect of resource provision of enterprises are financial and information support, which are manifested through protection against financial fraud and cyber attacks, the need to diversify sources of financing of enterprises, optimization of logistics aimed at reducing the company’s dependence on a single supplier, as well as the possibility of introducing alternative and renewable resources. Technological risks associated with the development of Industry 4.0 require new approaches to resource provision, introduction of digital technologies for monitoring and management of resources. The article analyzes the peculiarities of formation and implementation of the ERP system as a tool for optimizing business processes related to the effective planning and use of enterprise resources. The introduction of ERP systems is an important tool for improving the enterprise resource management system, which allows to ensure its flexibility, adaptability and high efficiency in a dynamic market environment. Thus, effective resource management ensures the stable development of the enterprise, allows the introduction of the latest technologies, implementation of investment projects, development of mathematical models for resource assessment, and decision-making to prevent crisis situations.